Student Perception Of The Basic Engineering Learning Model Through The Play Approach - siti ayu risma putri; Muhsana El Cintami Lanos; Hikmah Lestari; Mutiara Fajar (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
AbstractThis study aims to determine students' perceptions of the volleyball basic technique learning model through a play approach based on (1) Perceptions of learning knowledge of basic volleyball techniques, (2) Perceptions of teacher teaching styles, (3) Perceptions of the media used are easy to use, (4) Perceptions about the interest in learning basic volleyball techniques, (5) Perceptions about the need to develop a volleyball basic technique learning model through a play approach were obtained. This research is a descriptive quantitative research. The results of this study indicate that (1) Perceptions of basic volleyball technique learning knowledge obtained a value of 95% in the very good category, (2) Perceptions of the teacher's teaching style obtained a value of 73.13% in the good category, (3) Perception of the media which is used easy to use obtained a value of 85% with a very good category, (4) Perceptions about the interest in learning the basic techniques of volleyball obtained a value of 95% with a very good category, (5) Perceptions about the need to develop a volleyball basic technique learning model through the playing approach obtained the value is 100% in the very good category, which means that students agree if the development of a volleyball basic technique learning model through a playing approach is developed. The results of this study indicate that students' perceptions of the development of a volleyball basic technique learning model through a play approach in junior high schools in Palembang are positive, for that it is necessary to develop a volleyball basic technique learning model through a play approach.Keywords: Student perceptions, basic techniques, volleyball, playing